2019
DOI: 10.4103/ijpvm.ijpvm_471_17
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of barriers and enablers of retention in a program to reduce vertical transmission of HIV at health centers in Zimbabwe

Abstract: Background: Poor retention in the prevention of women in prevention of vertical transmission programs remains a formidable common setback in elimination of HIV/AIDS. It creates new problems such as poor health outcomes and increased incidence of vertical transmission of HIV. There is a dearth of qualitative information to explain poor retention of women in prevention of mother-to-child transmission (PMTCT) programs in Zimbabwe. The purpose of the study was to explore the enablers and barriers of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The participants commended the positive attitude of the HCWs, which facilitated a good provider-patient relationship, helped them to cope with the HIV-positive test results, and encouraged their continued participation in PMTCT. Similar observations were found in other studies as well [19,28,29]. The study found that the integration of PMTCT with other antenatal services helped to minimise the stigma associated with living with HIV.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The participants commended the positive attitude of the HCWs, which facilitated a good provider-patient relationship, helped them to cope with the HIV-positive test results, and encouraged their continued participation in PMTCT. Similar observations were found in other studies as well [19,28,29]. The study found that the integration of PMTCT with other antenatal services helped to minimise the stigma associated with living with HIV.…”
Section: Discussionsupporting
confidence: 90%
“…The positive perception about PMTCT served as a motivation for them to enroll in PMTCT. In this study and prior studies in SSA, the drive to enroll in PMTCT arose from the mother's desire to protect their babies from HIV infection [7,19,20,34,48]. The women enrolled in PMTCT understood that they could prevent HIV from transmitting from the mother to the baby by taking and adhering to ART.…”
Section: Discussionmentioning
confidence: 96%
“…Peer support services have been widely in use to mitigate barriers of uptake, adherence and outcomes in HIV and PMTCT services in low-and middle-income countries [10][11][12]. The motivation for peer support services has been partly driven by challenges of human resource shortages in understaffed overburdened health care systems, and also the demand for counselling, adherence and psychosocial support among women receiving PMTCT care [10,[13][14][15][16][17]. Although there is rich qualitative literature on the engagement of peer-mothers in PMTCT care [14,[18][19][20], the literature remains scarce on quantitative evaluation of the effect of peermothers on PMTCT outcomes, specifically ART adherence and retention, viral suppression and MTCT, in the era of lifelong ART for PMTCT [10][11][12]21].…”
Section: Introductionmentioning
confidence: 99%
“…10 Prohibitive financial requirements for clinical visits and nutritional needs while on ART along with drug-related side effects can pose further challenges. 12 In the face of these barriers, ensuring continuity of care for MIPs in countries with high rates of vertical transmission requires prioritized engagement of MIPs until cessation of breastfeeding, so they may receive the full package of prophylaxis and support services and timely infant HIV testing in line with WHO guidelines. Without such continuity in care, infants with HIV remain undiagnosed and untreated with resulting high rates of mortality: 12% of infants living with HIV will die by age 2 to 3 months, 35% by 1 year and 52% by the age of 2 years.…”
Section: Introductionmentioning
confidence: 99%